Pengaruh Profitabilitas, Struktur Modal Terhadap Nilai Perusahaan dengan Ukuran Perusahaan Sebagai Moderasi - Kurniawan, Priscilla Angel; Menik Indrati (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
The study was conducted to investigate how profitability, capital structure, and company size affect company value, company size acts as a moderator variable. There are independent variables Profitability and Capital Structure and dependent variables, Company Value, while Company Size acts as a moderator factor. The study focused on companies in the healthcare sector listed on (IDX) from 2021 to 2023, and identified 13 companies that met the established criteria, resulting in a total of 39 observation data points. The analysis used the panel data regression method, with Econometric Views (Eviews). The findings of this study reveal that profitability has a significant positive impact on company value. The value of a company is positively influenced by its capital structure. In addition, company size plays an important role in moderating profitability and company value, as well as the relationship between capital structure and company value. This study is a valuable consideration for investors and shareholders when evaluating financial statements to make investment decisions.